Modul Penentuan Hukum Makanan Ubah Suai Genetik (GMF) Dan Kepentingannya Kepada Umat Islam - Mohd Tahir, Sharif; Mohd Kashim, Mohd Izhar Ariff (Jurnal Fiqh, 2016)
This article discusses the importance of building the module to determine the status of genetically modified food (GMF) and its importance to Muslims based on Maqasid Shariah. GMF is a modern food products produced through biotechnology engineering with methods to manipulate the deoxyribonucleic acid (DNA) of plant, animal and so on. As a result, the process produces food which are more nutritious and contain more nutrients than natural food products. GMF are also able to be produced in large quantities and incur little cost compared to natural food through genetic modification process. There is still no any guidelines or module that can be used to determine the ruling status of the GMF products. The objective of this study is to produce guidelines in module that should be used in determining the status of GMF that had been through biotechnology engineering process. Further, this study also seeks to clarify the importance of guidelines to determine the ruling status of GMF for Muslims. To make this study successful, data collection was conducted by using a qualitative design using library methods, descriptive, comparative, and content analysis of the sources in fiqh and science. Through the research conducted, GMF products can be eaten if they suit certain principles that have been outlined. Through these principles, the application of the ruling determines the products of GMF will be more organized. This study is significant to overcome the ambiguity of the ruling status of the GMF. It also aims to help the relevant authorities in determining the ruling of the products based on GMF products.